Σεβαστή Τρουμπέτα, Christian Voss (επιμ.), 2003, «Minorities in Greece. Historical issues and new perspectives», History and culture of South Eastern Europe, An Annual Journal, 5, Slavica Verlag,Μόναχο - Πετρονώτη, Μαρίνα (The Greek Review of Social Research, 2016)
Δε διατίθεται περίληψη / no abstract available